Influence of Conventional, CAD-CAM, and 3D Printing Fabrication Techniques on the Marginal Integrity and Surface Roughness and Wear of Interim Crowns - Nada Aldahian; Rawaiz Khan; Mohammed Mustafa; Fahim Vohra; Ali Alrahlah (Applied Sciences, 2021)
The aim is to assess the influence of fabrication techniques—conventional (CN), CAD-CAM (CC), and 3D printing (3D)—on the marginal fit, adaptation, surface roughness, and wear of interim restorations of crowns. Thirty interim crowns were fabricated using CN, CC, and 3D techniques. Sixty discs were fabricated to evaluate surface wear and surface roughness properties, with 10 disc samples in each group (n = 10). Internal adaptation and marginal integrity of interim crowns were analyzed with micro CT to detect microgaps at selected points. Average surface micro-roughness (Ra) was calculated in micrometers (μm) using an optical non-contact surface microscope under cyclic loading. Surface wear was evaluated by surface area measurements (mm3) using a micro CT. Analysis of variance (ANOVA) and Tukey’s post hoc comparison tests with Pearson correlation were performed for data analysis. The highest adaptation means were for CN (269.94 ± 64 μm), and the lowest mean value was observed for 3D (197.82 ± 11.72 μm) crowns. CN and CC specimens showed comparable adaptation (p > 0.05), which were significantly higher (p < 0.05) than 3D crowns. CN crowns showed significantly higher marginal misfit compared to 3D (p < 0.05) and CC (p < 0.05) crowns. The highest mean surface roughness was observed in the 3D crowns (5.61 ± 0.33 µm), whereas the lowest was found in CC crowns (3.28 ± 0.34 µm). Better restoration Ra was observed using the CC method followed by CN. CN had the highest wear (17.79 ± 2.78 mm3), and the lowest wear was observed in the 3D (10.81 ± 2.00 mm3) specimen. Low surface wear was observed using 3D printing, followed by CN and CC techniques. The printed specimen showed comparable outcomes to CAD-CAM restoration; however, they were better than CN restoration. A positive correlation between adaptation and surface roughness was observed, indicating an effect of the fabrication technique on material physical property.